Problems with perfect-looking two-needle decorative seams in the manufacture of leather car seat covers. Issue 1 (January 2020) - Zelova, Katarina; Glombikova, Viera; Havelka, Antonin
This study objectively evaluates the uneven appearance of the two-needle decorative seams of leather seat covers. The investigation is based on both measurement of the stitch slant angle by image analysis and measurement of the penetration force influenced by different cutting points of the needles. To record the unevenness the new parameter, the difference of the stitch slant between the right- and left-hand sides of the seam was evaluated. Further, the interrelation ship among penetration force differences of the stitch slant and type of needle point was searched for to meet the requirements of car producers for a perfect appearance of decorative seams. The degree of uneven seam was measured within subjective visual evaluation, too. Four natural and two artificial leathers were tested. A combination of two threads and four needle points was applied to the tested leathers. It was confirmed that the uneven appearance was influenced by the type of leather, the point of the sewing needle and by the sewing thread. The selection of the needle point influenced the size of the force required for penetrating the leather. It was determined only in half of the cases that the smaller the force of penetration, the more even the appearance of the decorative seam. In most cases, using the cutting point LR, the left seam looked less slanted than the right one. Conversely, when using the cutting point for straight stitch appearance, that is, DH, the left stitch looked straighter than the right one. The causal link between the new parameter Δ β and the suitability of the applied needles and threads for leather materials was found.